"Professional WinFX Beta: Covers ""Avalon"" Windows Presentation Foundation and ""Indigo"" Windows Communication Foundation" - David (Jean-Luc); Ryan (Bill); Deserranno (Ron) (2006)
Windows Presentation
22.5
Keywords: Windows Presentation